PENGUATAN BUDAYA LITERASI PADA ANAK USIA DINI MELALUI “GERNAS BAKU” - Zaidatul Arifah (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2018)
Writing this journal aims to find out how to strengthen the culture of literacy in early childhood and how the implementation of strengthening literacy culture in early childhood through "Baku Gernas". The background of strengthening literacy culture at an early age through "Baku Gernas" is the low literacy culture in Indonesia. Whereas early age is a golden age to instill literacy because they are experiencing a rapid developments in the field of language. This study uses descriptive qualitative methodology. The data collection techniques in the study used documentation techniques through literature. Based on the results of the study, the authors found that to strengthen the culture of early childhood literacy in the family sphere there were five focus of strengthening which included several strategies. They are strengthening through fostering children's interest in reading, strengthening through parental involvement, strengthening through many and varied reading resources. strengthening through habituation, strengthening by utilizing the environment and technology. Gernas Baku can be implemented through parents understanding the developmental stages of children's reading and language, parents trying to foster children's interest in reading, parents understand and provide reading materials according to the child's development stage, parents get used to reading books / reading or telling stories with children through various techniques, parents invite children to visit literacy places in the environment, parents take part in introducing literacy reading and Penulisan jurnal ini bertujuan untuk mengetahui bagaimana penguatan budaya literasi pada anak usia dini dan bagaimana implementasi penguatan budaya literasi pada anak usia dini melalui “Gernas Baku” . Latar belakang penguatan budaya literasi pada usia dini melalui “Gernas Baku” yaitu rendahnya budaya literasi di Indonesia. Sedangkan usia dini adalah usia emas untuk menanamkan literasi karena mereka pengalami perkembangan pesat dalam bidang bahasa. Penelitian ini menggunakan metodologi kualitatif deskriptif. Adapun teknik pengambilan data dalam penelitian menggunakan teknik dokumentasi melalui studi pustaka. Berdasarkan hasil penelitian, penulis menemukan bahwa untuk menguatkan budaya literasi anak usia dini di ranah keluarga terdapat lima fokus penguatan yang memuat beberapa strategi, antara lain penguatan melalui menumbuhkan minat baca anak, penguatan melalui keterlibatan orang tua, penguatan melalui sumber bacaan yang banyak dan beragam, penguatan melalui pembiasaan, penguatan dengan memanfaatkan lingkungan dan teknologi. Gernas Baku dapat diimplementasikan melalui orang tua memahami tahap perkembangan membaca dan bahasa anak, orang tua berusaha menumbuhkan minat baca anak, orang tua memahami dan menyediakan bahan bacaan sesuai tahap perkembangan anak, orang tua membiasakan membacakan buku/bacaan atau bercerita dengan anak melalui berbagai teknik, orang tua mengajak anak untuk mengunjungi tempat-tempat literasi di lingkungan, orang tua ikut andil memperkenalkan membaca dan menulis keaksaraan.